Temperature‐Induced Stacking to Create Cu2O Concave Sphere for Light Trapping Capable of Ultrasensitive Single‐Particle Surface‐Enhanced Raman Scattering. (22nd June 2018) - Li, Xiaoxia; Shang, Yang; Lin, Jie; Li, Anran; Wang, Xiaotian; Li, Bin; Guo, Lin
Abstract: The fabrication of bowl or concave particles with "asymmetric centers" has drawn considerable attentions, in which multiple scattering occurs inside the particles and the ability of light scattering is distinctly enhanced. However, the limited variety of templates, the uncontrollable dimensions such as the size of concavity and the complex growth process have posed serious limitations to the reproducible construction of concave particles with desired geometries and their light‐trapping properties. Herein, a "temperature‐induced stacking" strategy is proposed to create controllable concavity Cu2 O spheres for the first time. Different sizes of F68 micelles can be formed through aggregation under different reaction temperatures, which can serve as soft template to tailor concave geometries of Cu2 O spheres. The as‐prepared Cu2 O concave sphere (CS) can serve as single‐particle (SP) surface‐enhanced Raman scattering (SERS) substrate for highly repeatable and consistent Raman spectra. The unique cavity of Cu2 O CS entraps light effectively, which also enhances the scattering length owing to multiple light scattering. Combined with slightly increased surface area and charge‐transfer process, Cu2 O CS exhibits remarkable single‐particle SERS performance, with an ultralow low detection limit (2 × 10 −8 mol L −1 ) and metal comparable enhancement factor (2.8 × 10 5 ). Abstract : Temperature‐induced stacking for creating Cu2 O concave spheres (CSs) is developed for the first time. Different sizes of F68 micelles form under different temperatures, which can tailor the concavity of Cu2 O CSs. The Cu2 O CS exhibits a remarkable single particle surface‐enhanced Raman scattering performance with ultralow limit of detection (2 × 10 −8 mol L −1 ) and metal comparable enhancement factor (2.8 × 10 5 ).